1990
DOI: 10.4319/lo.1990.35.3.0597
|View full text |Cite
|
Sign up to set email alerts
|

A microalgal growth model

Abstract: Recent experimental evidence has made it clear that effects of irradiance and nutrient limitation on light absorption and photosynthetic quantum yields of microalgae and the relationship between cellular N : C ratios and nutrient-limited growth rates are inconsistent with the assumptions and predictions of current models of algal growth. A new algal growth model was therefore developed to overcome these inconsistencies. The new model predicts a hyperbolic relationship between nutrient-saturated growth rates an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 27 publications
3
32
1
Order By: Relevance
“…Geider et al (1996Geider et al ( , 1998 and Flynn et al (1997) were the first to employ dynamic acclimation models to phytoplankton growth and physiological acclimation. Unlike previous models, which were based on balanced growth under prescribed but invariant environmental conditions (Bannister 1979, Shuter 1979, Kiefer & Mitchel 1983, Laws & Chalup 1990, the dynamic models were developed for application to variable Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…Geider et al (1996Geider et al ( , 1998 and Flynn et al (1997) were the first to employ dynamic acclimation models to phytoplankton growth and physiological acclimation. Unlike previous models, which were based on balanced growth under prescribed but invariant environmental conditions (Bannister 1979, Shuter 1979, Kiefer & Mitchel 1983, Laws & Chalup 1990, the dynamic models were developed for application to variable Fig. 8.…”
Section: Discussionmentioning
confidence: 99%
“…Respiration: Laws & Chalup (1990) reported values of 0.03 d -1 for maintenance respiration and 0.28 for active respiration. Other investigators have found that from 15 to 35% of carbon fixed is lost to metabolism (Groeger & Kimmel 1989, Kiddon et al 1995.…”
Section: Modelmentioning
confidence: 99%
“…The cellquota approach has been used to construct phytoplankton growth models describing the interactions of light and nutrient limitation (e.g. Laws & Chalup 1990, Geider et al 1998), but few attempts have been made to include effects of different nutrient elements in a mechanistic theory (Flynn 2001, Flynn 2008. Colimitation by several nutrients has been classified on a theoretical basis by Arrigo (2005), who distinguished direct effects of nutrient concentration (multi-nutrient colimitation), organismlevel effects (biochemical colimitation) and populationlevel effects (community colimitation).…”
Section: Introductionmentioning
confidence: 99%